Real-world evaluation of JBA Glucotrojan® supplementation in regulating postprandial glycemic response in healthy adults - Repizo, Guillermo Daniel; Huan, Le Quang; Yong, Shin Jie; Sethaputra-Piccin, Bude (Progress in Nutrition, 2025)
Background and aim: Our modern diet, abundant in carbohydrates and sugars, often causes surges in blood glucose levels that facilitate the development of diabetes and obesity. This public health crisis has propelled the innovation of GlucoTrojan®, a blend of white mulberry leaf, mango leaf, and banana stem juice extracts. Our study aims to examine the effects of GlucoTrojan® on the postprandial blood glucose response after consuming white rice. Methods: We conducted a real-world, prospective interventional study (clinicaltrials.gov registration: NCT06509204) to examine the effects of consuming cooked white rice (82 g of net carbohydrates) with and without GlucoTrojan® on postprandial blood glucose levels among healthy individuals. A continuous glucose monitoring (CGM) device was used to measure blood glucose levels. Tastermonial mobile application was used to collect data on food and drink consumption. The incremental area under the curve (iAUC) measuring glycemic index and postprandial glucose spikes were calculated to assess the effects of GlucoTrojan®. Results: Of the 50 individuals who participated, 25 (mean age of 40.3 years; 36% females) provided complete and valid data for analyses. Consuming white rice with GlucoTrojan® significantly reduced the mean postprandial blood glucose levels by 14 ± 6 mg/dl (P < .0001) over 2 hours compared to white rice consumption alone, corresponding to a 26.1% reduction. GlucoTrojan® also significantly lowered the glycemic index of white rice by a mean of 1166 ± 610 mg/dL × min, equivalent to a 33% reduction compared to no GlucoTrojan® (P < .0001). Conclusions: The findings indicate that GlucoTrojan® significantly modulates postprandial glucose responses, lowering blood glucose levels and glycemic index. Overall, our study supports GlucoTrojan® as a promising supplement for managing blood glucose levels.